2020
DOI: 10.1007/s00701-020-04507-2
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery may lower mortality in patients suffering from severe spinal infection

Abstract: Purpose Spinal infection (SI) is a life-threatening condition and treatment remains challenging. Numerous factors influence the outcome of SI and both conservative and operative care can be applied. As SI is associated with mortality rates between 2 and 20% even in developed countries, the purpose of the present study was to investigate the occurrence and causes of death in patients suffering from SI. Methods A retrospective analysis was performed on 197 patients, categorized into two groups according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…In a retrospective study, Lener et al reported that the operative cohort had lower mortality rates than the conservative cohort (6% versus 18%) 8 . As a result, the authors recommended early surgical treatment, particularly in patients with septicaemia or progressive spinal infection 8 .…”
Section: Timing Of Surgical Interventionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective study, Lener et al reported that the operative cohort had lower mortality rates than the conservative cohort (6% versus 18%) 8 . As a result, the authors recommended early surgical treatment, particularly in patients with septicaemia or progressive spinal infection 8 .…”
Section: Timing Of Surgical Interventionmentioning
confidence: 99%
“…Generally, patient outcome is directly correlated with the disease severity and the time between diagnosis and actual treatment [7]. In a retrospective study, Lener et al reported that the operative cohort had lower mortality rates than the conservative cohort (6 % versus 18 %) [8]. As a result, the authors recommended early surgical treatment, particularly in patients with septicaemia or progressive spinal infection [8].…”
Section: Timing Of Surgical Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSD can be treated conservatively or surgically [ 3 , 4 ], and can affect a single level or multiple levels. Patients benefit from early surgical treatment of PSD and spinal infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%